Cell-free DNA and neuromediators in detecting aggressive variant prostate cancer - Hardenberg, Jost von; Worst, Thomas; Westhoff, Niklas Christian; Erben, Philipp; Bolenz, Christian; Weiß, Christel (Oncology research and treatment, 2018)
BACKGROUND: Aggressive variant transformation in metastatic castration-resistant prostate cancer (mCRPC) represents an under-recognized phenomenon. There is an urgent need for non-invasive biomarkers to detect these variants and identify treatment alternatives. - METHODS: A prospective observational pilot study in mCRPC patients receiving treatment with cabazitaxel (CAB) was conducted. Neuromediators were sequentially evaluated and their impact on disease endpoints calculated. Targeted next-generation sequencing (NGS) of cell-free DNA (cfDNA) was also performed in a highly pretreated subset of patients. - RESULTS: 23 patients were included. Estimated effects indicate that neuron-specific enolase (NSE) levels at baseline may be correlated with overall survival (NSE unit 18.3 ng/ml: HR1.262 (95% confidence interval (CI) 0.985-1.616)) and that chromogranin A (CGA) may be correlated with progression-free survival (CGA unit 98.1 ng/ml: HR1.341 (95% CI 1.011-1.778)). cfDNA analysis revealed mutations annotated in prostate cancer (PCA) and small cell cancers (SCC). 1 patient showed elevated neuromediators along with annotated mutations in PCA and SCC, potentially indicating aggressive variant cancer. In 3 patients KIT mutations (e.g. pM541L, pV654A) known to be tissue-based biomarkers with level 1 evidence for the treatment with imatinib and sunitinib were found. - CONCLUSIONS: Sequential analysis of neuromediators and targeted NGS of cfDNA provide insight for the estimation of tumor heterogeneity under therapy with CAB.
Gesehen am 05.04.2019